Next-Generation Sequencing Enhances the Diagnosis Efficiency in Thyroid Nodules - Tan, Li-Cheng; Liu, Wan-Lin; Zhu, Xiao-Li; Yu, Peng-Cheng; Shi, Xiao; Han, Pei-Zhen; Zhang, Ling; Lin, Liang-Yu; Semenov, Arseny; Wang, Yu; Ji, Qing-Hai; Ji, Dong-Mei; et al. (Frontiers in Oncology, 2021)
Background Though fine-needle aspiration (FNA) improved the diagnostic methods of thyroid nodules, there are still parts of nodules that cannot be determined according to cytology. In the Bethesda system for reporting thyroid cytopathology, there are two uncertain cytology results. Thanks to the development of next-generation sequencing technology, it is possible to gain the genetic background of pathological tissue efficiently. Therefore, a combination of the cytology and genetic background may enhance the accuracy of diagnosis in thyroid nodules. Methods DNA from 73 FNA samples of thyroid nodules belonging to different cytology types was extracted and exome sequencing was performed by the ThyroLead panel. Test for BRAF mutation was also performed by ARMS-qPCR. Information including age, sex, preoperative cytology, BRAF mutation status tested by ARMS-qPCR, and surgical pathology was collected in electronic medical record system. Results A total of 71 single nucleotide variants, three fusion gene, and two microsatellite instability-high status were detected in 73 FNA samples. BRAF V600E mutation is the most common mutation in these malignant thyroid nodules. After combining the cytology and genetic background detected by next-generation sequencing, the diagnosis sensitivity was increased from 0.582 (95% CI: 0.441–0.711) to 0.855 (95% CI: 0.728–0.930) (P < 0.001) in our group, while the specificity, 1,000 (95% CI: 0.732–1.000) compared to 0.857 (95% CI: 0.562–0.975) (P = 0.25), did not get affected. Conclusions Next-generation sequencing in thyroid nodules can enhance the preoperative diagnosis sensitivity by fine-needle aspiration alone. It can also provide genetic background for direction of medication. It is possible for clinicians to combine cytology with genetic alterations for a more precise diagnosis strategy of thyroid nodules.